Videogames and their Impact on Education as a Teaching-Learning Tool: A Systematic Review of the Literature between the Years 2012-2022 (LACCEI, 2024)
The video game industry has grown in recent times and its use in the educational field has been happening cautiously, since there are still doubts regarding its contribution to the learning process. The objective of this research was to know the impact of video games on the teaching-learning process to provide success stories and recommendations for their correct application. A systematic review of the literature was carried out based on the results of the Google Scholar database, using the key terms "video games", "teaching", "learning" and "education”. Literature reviews, original articles and reports published between the years 2012 and 2022, written in Spanish and English, were selected. The initial search obtained 101 documents, of which 28 articles were selected and included in the review, applying the inclusion and exclusion criteria. It was possible to identify the positive impact of video games in the teaching-learning process, but studies of larger populations are still pending, not only at a local level.